2012
DOI: 10.5402/2012/607906
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Vaginal Progesterone as a Tocolytic Agent: Randomized Clinical Trial

Abstract: Vaginal progesterone has a potential beneficial effect in postponing of preterm labor by suppression of prostaglandins cascades. Although different studies evaluated the use of progesterone for preterm birth, the exact effect of which on prolongation of pregnancy remains unclear. Seventy two women who underwent preterm labor were managed by magnesium sulfate. Then they were randomly assigned to continue pregnancy either by applying vaginal progesterone (400 mg) until delivery or without using any drug. Gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 39 publications
3
20
0
2
Order By: Relevance
“…The details of the included trials are presented in Table 1 . Two trials employed oral progesterone [ 12 , 13 ], three used intra-muscular 17-hydroxyprogesterone caporate [ 14 16 ], our trial and seven others used vaginal progesterone [ 17 23 ] and one trial compared intramuscular 17-hydroxyprogesterone caporate or vaginal progesterone to no treatment [ 24 ]. Eight authors were contacted by email requesting additional information regarding outcomes not reported in their manuscripts and responses were received from three.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the included trials are presented in Table 1 . Two trials employed oral progesterone [ 12 , 13 ], three used intra-muscular 17-hydroxyprogesterone caporate [ 14 16 ], our trial and seven others used vaginal progesterone [ 17 23 ] and one trial compared intramuscular 17-hydroxyprogesterone caporate or vaginal progesterone to no treatment [ 24 ]. Eight authors were contacted by email requesting additional information regarding outcomes not reported in their manuscripts and responses were received from three.…”
Section: Resultsmentioning
confidence: 99%
“… Progesterone 200 mg vaginally/Placebo. Briery [ 16 ] 2014 USA 45 20–30 weeks gestation, tocolysis with NSAIDS, nifedipine or MgSO4 17-hydroxyprogesterone caporate 250 mg IM weekly/ Placebo Gargari [ 23 ] 2012 Iran 110 24–33 weeks gestation, tocolysis with MgSO4 Progesterone 400 mg vaginally/No treatment Wood 2017 Canada 41 23–33 weeks gestation, after tocolysis with NSAIDS or nifedipine or no tocolysis and positive vaginal fetal fibronectin Progesterone 200 mg vaginally/Placebo. …”
Section: Resultsmentioning
confidence: 99%
“…Yet since no study directly compared the efficacy of 100 and 200 mg, there is no explicit evidence on which dosage has greater effect in preventing PTB. Vaginal progesterone suppository was dosed either 200 or 400 mg when used in twin pregnancies [ 28 29 30 31 ] or as a treatment after inhibition of preterm labor [ 32 33 34 35 36 ], but the optimal dose and its efficacy in twin pregnancies and preterm labor requires further evidence.…”
Section: Type Routes Dose and Interval Of Administrationmentioning
confidence: 99%
“…In various studies improvement in birth weight ranged from 290-490 gms. 11,[13][14][15]18 NICU admission were also less in study group(14% vs 24%) with shorter nursery stay(7.71 vs 8.41 days).Neonatal complications like RDS, sepsis, mechanical ventilation were also less in study group. There was one case of neonatal death in Group II.…”
Section: Discussionmentioning
confidence: 72%
“…Results are similar as reported in literature though progesterone, dose and route are different in various studies. 11,[13][14][15][16] Borna et al reported difference in prolongation of pregnancy by 11.5 days while Gargari et al reported it to be 2.6 weeks. Bomba-Opon et al observed a significant reduction in delivery before 34 weeks with vaginal progesterone (9.8% in progesterone group versus 35.3% in control group; p = 0.002).…”
Section: Discussionmentioning
confidence: 99%